Total quality management of the philippine national police crime laboratories in region v - Lomatao, J Paris Rock Austria (San Miguel, Iriga City: University of Saint Anthony, 2012)
Total quality management of the philippine national police crime laboratories in region v.
Includes bibliographical references.
English
Keywords: Quality management